Short-term results of synovectomy and total knee arthroplasty in patients with diffuse-type pigmented villonodular synovitis - Bansal, Aakash; Meena, R. P.; Singh, Prince; Meena, Umesh Kumar; Yadav, Bhavyaraj Singh; Kharalwa, Rohit (International Journal of Research in Orthopaedics, 2025)
Background: Diffuse-type pigmented villonodular synovitis (D-PVNS) is a rare, benign proliferative condition that affects the knee joint, often leading to subchondral bone erosion, cyst formation, and ultimately secondary osteoarthritis. This study aimed to assess the short-term clinical outcomes of synovectomy combined with total knee arthroplasty (TKA) in patients diagnosed with D-PVNS. Methods: This study was conducted in the department of orthopaedics at government medical college, Kota, between 2020 and 2025, 28 patients with histopathologically confirmed D-PVNS of the knee underwent synovectomy followed by TKA. Clinical and operative data were recorded perioperatively and throughout follow-up to evaluate surgical effectiveness. Results: There were no intraoperative complications. The mean operative time was 73.4 minutes (range: 47-115 minutes), and the average estimated blood loss was 223.9 mL (range: 50-600 mL). Patients were followed up for an average of 58.7 months (range: 36-84 months). Range of motion improved from a mean of 86.1°±11.3° preoperatively (range: 60°-100°) to 107°±11.4° postoperatively (range: 90°-130°). The average knee society clinical score increased from 38.9±9.5 to 84.4±6.1, while the functional score improved from 48.9±13.1 to 84.6±6.1 (p<0.05). Postoperative radiographs revealed no signs of prosthesis loosening, dislocation, or periprosthetic fracture. Conclusions: Synovectomy combined with total knee replacement offers favorable short-term outcomes in managing D-PVNS of the knee, with significant improvements in joint function and stability and no major complications observed during follow-up.